Motivação dos recursos humanos:o caso dos auditores-fiscais da Receita Federal - Gomes, Alcindo Arcenio Pinheiro (2003)
The study here presented makes an approach on job satisfaction and niotivation of the employees of a public federal organization. lt is based on the intrinsie motivation tbeory line, on Maslow s needs theory, and on Herzberg s motivation-hygiene theory, and follows a quantitative methodoiogy with descríptive research, applied research and case study characteristies. Its results indicate that the employees general satisfaction level is below the medium grade of a satisfaction grade scale that varies from 1 to 6. The security needs,followed by the physiokgical ones, are the least satisfïed, while the autorealization needs are the most satisfied; salary, security and policies and administration are the factors of hygiene that have the biggest weight on employees dissatisfaction, whilst the factor that least contributes for dissatisfaction is interpersonal relationship. Among the motivators, what most positively affects motivation to work is the achievement factor, while Lhe advancement and the personal growth are the ones that least contribute for that motivation. The study also underlines the correspondence and interdependence among human basic needs and the factors of hygiene and motivators; focalizes the influence of these needs and factors satisfaction levei over employees motivation, and presents a practical purposive diagnostic. And, on its conclusion, the study points out the necessity of changing the management system and of adopting a policy that takes into account the human resources satisfaction and motivation.